Clinico-Pathological Atlas of Cardiovascular Diseases - Lucena, Joaquín S.; García-Pavía, Pablo; Suarez-Mier, M. Paz; Alonso-Pulpon, Luis A. (Springer International Publishing : Imprint: Springer, 2015)
This atlas reviews the spectrum of pathologies affecting the structures of the cardiovascular (CV) system most frequently encountered in sudden cardiac deaths, and has been conceived as a first step for making CV pathology diagnoses. It is almost impossible to establish an accurate diagnosis based only on morphology, and therefore this atlas is to assemble knowledge and points of view from two medical specialties, cardiology and forensic pathology. It has been designed as a practical visual reference that includes a summary of clinical characteristics, many high quality images and clear tables containing the main morphological characteristics of each disease.   Clinico-Pathological Atlas of Cardiovascular Diseases has been written by cardiologists and forensic pathologists and histopathologists, which enables a combination approach in each chapter, to produce a thorough resource that will be of relevance to a wide range of specialists, including cardiologists, cardiac surgeons, interventional cardiologists, forensic doctors, and pathologists.